STRESS AND EMOTIONAL INTELLIGENCE IN STUDENTS AT THE ISLAMIC BOARDING SCHOOL - Nadya Safira Sugiarto; Maya Oktaviani; Vania Zulfa (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2023)
This research aims to analyze the effect of stress on students' emotional intelligence. This research uses the associative quantitative method. This research was conducted from June to November 2021 at Senior High School El-Nur El-Kasysyaf Islamic Boarding School, Bekasi, West Java. The population in this study was high school students of El-Nur El-Kasysyaf Islamic Boarding School, with a total sample of 150 respondents selected with the saturated sampling technique. Data was collected using the Adolescent Stress Questionnaire (41 items) and the Revised Emotional Intelligence Scale (33 items). The results showed a negative and significant effect of stress on students' emotional intelligence. The lower the stress level, the higher the students' emotional intelligence. Stress affects 9.5% of emotional intelligence, while the other 90.5% is affected by other factors not examined in the model. Therefore, there needs to be socialization, prevention, and handling efforts to deal with stress by the school to minimize stress on students. On the other hand, students must be more sensitive in recognizing what they feel about themselves and those around them.AbstrakPenelitian ini bertujuan untuk menganalisis pengaruh stres terhadap kecerdasan emosional siswa. Penelitian ini menggunakan metode kuantitatif asosiatif. Penelitian ini dilaksanakan pada bulan Juni sampai November 2021 di Pesantren El-Nur El-Kasysyaf, Bekasi, Jawa Barat. Populasi dalam penelitian ini adalah santri SMA Pondok Pesantren El-Nur El-Kasysyaf, dengan jumlah sampel sebanyak 150 responden yang dipilih dengan teknik sampling jenuh. Data dikumpulkan dengan menggunakan Adolescent Stress Questionnaire (41 item) dan Emotional Intelligence Scale versi revisi (33 item). Hasil penelitian menunjukkan adanya pengaruh negatif dan signifikan stres terhadap kecerdasan emosional siswa. Semakin rendah tingkat stres, semakin tinggi kecerdasan emosional siswa. Stres mempengaruhi 9,5% kecerdasan emosional, sedangkan 90,5% lainnya dipengaruhi oleh faktor lain yang tidak diteliti dalam model. Oleh karena itu, perlu adanya sosialisasi, pencegahan, dan upaya penanganan untuk mengatasi stres oleh pihak sekolah untuk meminimalisir stres pada siswa. Di sisi lain, siswa harus lebih peka dalam mengenali apa yang mereka rasakan tentang diri mereka sendiri dan orang-orang di sekitar mereka.